2016
DOI: 10.5539/ijps.v8n4p91
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Perceived Stress Level of University Students in Hong Kong

Abstract: Background. In the school year 2015/2016, a significantly increased suicide rate among students in Hong Kong raised alarm bells to the public. High levels of stress among Hong Kong students was believed to be one of the main causes of these suicide incidents. In order to examine the stress levels of Hong Kong students, we targeted the group of undergraduates and initiated this research study.Objective. This study aimed to provide more information and objective analysis with regard to the stress levels of under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
3
5
0
Order By: Relevance
“…The average PSS score for the present study was within the range of high perceived stress (M = 32.90; SD = 6.30). These findings reflect those of Kwok and Ng (2016) which associated university students with higher-than-average scores of perceived stress according to the PSS. Both findings are indicative of a need to develop educational strategy which promotes mental health resilience and healthy coping mechanisms.…”
Section: Discussionsupporting
confidence: 80%
“…The average PSS score for the present study was within the range of high perceived stress (M = 32.90; SD = 6.30). These findings reflect those of Kwok and Ng (2016) which associated university students with higher-than-average scores of perceived stress according to the PSS. Both findings are indicative of a need to develop educational strategy which promotes mental health resilience and healthy coping mechanisms.…”
Section: Discussionsupporting
confidence: 80%
“…Homesickness, on the other hand, would also have a major impact on international students' psychological well-being, especially in academic performance, eating and sleeping problems, and low energy and headache; this was also associated with cultural stress and depression among international students [4]. The study about international students from the Mainland of China reported 135 mainland Chinese students with 32% of prevalence of depression symptoms by Wei et al [1].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The issue of perceived stress does not only happen among the working population but also among university students. As [1] stated, a dramatically increased suicide rate among Hong Kong students raised alarm bells for the public in 2015/2016. One of the major causes of these suicide events is assumed to be high levels of stress among Hong Kong students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While episodes of EE may occur in response to positive emotions, studies of health-related effects of EE have predominantly examined EE behaviour as a response to negative emotional states such as stress, depression, boredom, and anxiety [ 6 – 10 , 22 , 23 ]. Studies from Western countries have reported that negative EE prevalence among college students ranges from 8.9 to 56% and negative EE was noted to be more common in females and those with higher levels of stress, depression, and anxiety [ 22 , 24 28 ]. Since individuals with negative EE tend to binge eat and consume highly caloric foods, negative EE has been associated with weight gain, overweight/obesity, difficulty in losing weight and sustaining weight loss, and even metabolic disorders across many age groups [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that negative EE may be prevalent among Chinese youths but the generalizability to other urban areas is unknown. University life has been noted to be extremely stressful in Hong Kong [ 24 , 38 , 39 ]. In comparison to other cities in China, Hong Kong, a former British colony, has a long history of Westernized fast-food and convenience store pre-packaged foods that are highly conducive to impulsive food consumption.…”
Section: Introductionmentioning
confidence: 99%